Innocent Until Presented - Pangaribuan, Aristo (Jurnal Hukum & Pembangunan, 2023)
This paper analyzes a practice of presenting suspects, which is a ritual that displays a suspect before the media. Until now, although it is frequently used by the police, there has been no attempt to examine such practices in Indonesia. In the criminal procedure scholarship, there is no standard term to describe it. This article will refer to such ritual as a presentation of suspects. This ritual has also been practiced around the world with different methods and has a long history, especially in the United States. This article discusses the presentation of suspects and question whether such a ritual is a violation of the fundamental rights of being presumed innocent until found guilty. Two issues will be examined to answer this question: The purported objectives for the practice and the accused’s right to be presumed innocent. The term innocence here is a presumptively innocent and not factually innocent. With that in mind, to some degree, this article realizes it would be permissible to deprive their liberty if it has a higher purpose.